Microstructure characterization and quantitative analysis of copper alloy matrix composites reinforced with WC-xNi powders prepared by spontaneous infiltration (Journal of Mining and Metallurgy, Section B: Metallurgy, 2018)
In this study, copper alloy matrix composites reinforced with WC particles with the addition of different Ni contents (0, 3, 5, 7, and 10 wt.%) were prepared by the spontaneous infiltration process. Image analysis was used to quantify the microstructural parameters, such as the particle size and distribution, area fraction, binder mean free path, pore size and porosity. The effect of Ni addition on the microstructure, density and hardness are discussed. The results show that a small addition of Ni improves the densification of the infiltrated composites. The quantitative analysis results are in good agreement with the microstructure properties and hardness results.